Student Mental Health and Psychological Supports at Pondok Pesantren: A Mixed-Method Case Study - Duna Izfanna; Mimi Fitriana; Much Hasan Darojat (Tazkiya Journal of Psychology, 2025)
The demand for mental health supports for students in the educational system is growing. As a distinct Islamic educational institution where students stay full-time in one community, Pondok Pesantren needs to provide supportive environment for students since their home life is separate and less supportive. Differences in background and adaptability can result in some students experiencing difficulties, feeling anxious, afraid, uncomfortable, isolated, and even deciding to move. It is essential to know the mental health condition of the students to identify early warning signs of mental health problems. The purpose of this study is to analyze the mental health of students in Pondok Pesantren Darunnajah, factors contributing to their mental health, and their coping methods in maintaining mental health. It used mixed method design, combining The Strength and Difficulties Questionnaires (SDQ Goodman) for quantitative data and interviews for qualitative insights. The questionnaire was conducted to 160 students, age 12-18 years old, using stratified sampling based on gender and class. 16 students and teachers were selected using purposeful sampling techniques and interviewed. The research found that the majority of student (79.4%) were classified as normal, 19.4% borderline, and 1.3% needing assistance. Peer problems had the lowest average value (2.46). Male students are higher on hyperactivity (5.39), while emotional difficulties are more common in female (4.40). There are five factors contributing the mental health; students’ adaptability, social skill, family support, teacher support, and religious belief. They maintained their mental health by having friends, enjoying lives and activities in Pondok Pesantren, also by enhancing religious beliefs and performing religious activities. The findings highlight the importance of providing psychological supports based on gender and class as well as integrating religious belief and social supports in promoting mental health within Pondok Pesantren.